Para conhecer a Terra: memórias e notícias de Geociências no espaço lusófono - M. H. Henriques (Documentos, 2012)
This work brings together a series of contributions presented at the 1st International Conference of Geosciences in the CPLP on 14th to 16th May 2012 in the Auditorium of the Rector's Office of the University of Coimbra. It presents works developed by various teams affiliated to different CPLP institutions, reflecting innovative research trajectories that describes and interprets objects and processes taking place inside or on the surface of the earth. The knowledge obtained contributes to the enrichment of traditional areas underpinning the geosciences and also emerging areas, whose limits of analysis are expanding to other planets.